Project works by the Institute of Archaeology named after A. Kh. Khalikov of the Tatarstan Academy of Sciences on preserving archaeological heritage sites (case study of Kazan) - Ekaterina V. Pashina; Ilnur Yu. Mirsiyapov (Археология евразийских степей, 2025)
The article deals with the works by the Institute of Archaeology named after A.Kh. Khalikov of the Tatarstan Academy of Sciences in the field of preserving archaeological heritage sites. The period under consideration spans 10 years, from the establishment of the Institute in 2014 to 2023 inclusive. The subject of analysis is project activities related to the development of documentation (documentation issues) that substantiate measures to ensure the preservation of cultural heritage objects. Geographically, the study is limited to the boundaries of the city of Kazan and areas of the urban cultural layer that are protected as places of interest. The aim of the work is to analyze the dynamics of project activities and the specific share of the Institute in this area of archaeological heritage preservation. It also includes an assessment of the territorial distribution of technogenic load on the cultural layer of Kazan. The Institute of Archaeology is the leading scientific organization in the region in the field of monument protection, while there is a significant increase in the activity of commercial organizations in this area.